Chondrodermatitis nodularis nasi. (13th September 2020) - Kasitinon, Stacy Yuan; Vandergriff, Travis
Abstract: Chondrodermatitis nodularis helicis is a relatively common ulcerative, inflammatory condition affecting the skin, and cartilage of the ear. We present a case of chondrodermatitis affecting the skin and cartilage of the nose, designated chondrodermatitis nodularis nasi . Clinically, chondrodermatitis presents as a singular, painful, ulcerated papule or nodule that results from prolonged pressure, trauma, sun exposure, or vascular compromise. The clinical features resemble those seen in skin cancer, and a biopsy is often required to secure the diagnosis. Histopathologic analysis of chondrodermatitis demonstrates a central ulcer, beneath which there is fibrinoid necrosis of the dermis and inflammatory infiltrates. The ulcer is bordered by pseudoepitheliomatous hyperplasia with underlying granulation tissue. In addition to a clinical and morphologic description of chondrodermatitis nodularis nasi, a discussion of etiological factors and differential diagnoses is included. Increased recognition and reporting of the condition will allow for the exploration of optimal treatment strategies.